Improvement of nisin production by using the integration strategy of co-cultivation fermentation, foam fractionation and pervaporation. (May 2021) - Liu, Wei; Zhou, Jingping; Tan, Fangdai; Yin, Hao; Yang, Chunyan; Lu, Ke
Abstract: In this work, an integrated strategy of fermentation and separation was developed to improve nisin production. During fermentation, the acidification of fermentation liquid would hinder the synthesis and maturation of nisin inside strain cells. First, Saccharomyces cerevisiae ( S. cerevisiae ) was co-cultivated with Lactococcus lactis subsp. lactis ( L. lactis ) to overcome above obstacle. Experimental results indicated that lactose could be used as the substrate carbon source of co-cultivation fermentation. When inoculation ratio of L. lactis and S. cerevisiae was 10 2 :1, nisin titer and ethanol concentration in the fermentation liquid were 3436.3 ± 171.8 IU/mL and 5.9 ± 0.2 mg/mL, respectively. Subsequently, glucose (500 g/L) was supplied into the culture at 24 h for further increasing nisin yield through the quorum sensing of microorganisms. Foam fractionation was used to recover nisin from fermentation liquid. Under the conditions of volumetric air flow rate 40 mL/min, pore diameter of gas distributor 180 μm and initial coupling time of fermentation and foam fractionation after sugar supplementation 9 h, enrichment ratio and recovery percentage of nisin reached 5.8 ± 0.2 and 63.1 ± 2.8%, respectively. Through integrating pervaporation after sugar supplementation for 9 h, permeate concentration and recovery percentage of bioethanol were 367.2 ± 16.5 mg/mL and 76.2 ± 3.4%, respectively. The total nisin titer was 4593.2 ± 206.6 IU/mL. Highlights: An integration strategy had been developed to improve nisin production. Co-cultivation fermentation was performed to metabolize lactic acid. Quorum sensing of strains was strengthened by supplying glucose. Nisin was recovered by coupling foam fractionation with fermentation. Pervaporation had been used to avoid cell damage from ethanol stress.